CYBER CRIMES IN THE COVID-19 PANDEMIC SCENARIO (CIPEEX, 2025)
This paper aims to analyze cybercrime in the context of the COVID-19 pandemic, addressing its constitutive elements, the main criminal types committed in the virtual environment, and the applicable Brazilian legal framework. The research demonstrates that the advancement of digital technologies, while bringing numerous benefits to society, has also facilitated the practice of illegal acts in cyberspace. During the pandemic, the increased use of digital platforms, driven by social isolation, led to a significant rise in cybercrime occurrences, such as electronic fraud, device intrusion, crimes against honor, scams, and data breaches. The study is based on qualitative and bibliographical methodology, utilizing legal doctrines, specific legislation, and data from institutions such as CERT.br and NIC.br. It is concluded that, despite legislative progress, effectively tackling cybercrime requires constant updating of laws, strengthening international cooperation, and developing public policies for digital education.
Keywords: Cybercrime; Criminal Law; Covid-19 pandemic; Legislation; Digital security